Mapping the Evolutions and Trends of Literature on Wayfinding in Indoor Environments - Hessam Ghamari; Ayyoob Sharifi (MDPI AG, 2021)
Research on indoor wayfinding has increased in number and significance since the 1980s. Yet, the information on wayfinding literature is now difficult to manage given its vast scope and spread across journals, institutions, disciplines, and themes. While there is an increasing number of publications within this rapidly growing field of research, there are limited review studies in the field, and there is still missing an overall analysis of the current state of wayfinding literature and its evolution. The main objective of this study is to present a bibliometric analysis of about forty years of research on indoor wayfinding to provide an overview of the research landscape. The final database of the study contained 407 publications. VOSviewer was used as a science mapping software tool to identify major focus areas and to identify influential authors, publications, and journals using various network analysis techniques, such as term co-occurrence, co-citation, and bibliographic coupling. Similar co-occurrence analysis was used to understand how the intellectual base of the field has evolved over time and what the major themes are that have contributed to this evolution. The results show that this field has initially been mainly focused on few themes but has later become more diversified to acknowledge the multi-dimensional characteristics of indoor wayfinding. While spatial knowledge acquisition and cognitive maps are still dominant core areas, there are topics, such as signage, isovists, and the use of eye-tracking and virtual reality, that still need to be further investigated.